CD94-driven in vitro expansion of highly functional adaptive NKG2C+ NKG2A- CD57+ NK cells from CMV+ healthy donors - Giordano, Chiara; Carlomagno, Simona; Falco, Michela; Cantoni, Claudia; Vitale, Massimo; Caruana, Ignazio; Dirks, Johannes; Serio, Alberto; Muccio, Letizia; Bartalucci, Giulia; Bo, Alessandra; Locatelli, Franco; et al. (Frontiers in Immunology, 2025)
BackgroundAdaptive human natural killer (NK) cells are an NK cell subpopulation arising upon cytomegalovirus (CMV) infection. They are characterized by CD94/NKG2C expression, a mature CD57+KIR+NKG2A– phenotype, a prolonged lifespan, and remarkable antitumor functions. In light of these features, adaptive NK cells represent suitable candidate to design next-generation therapies, based on their enhanced effector function which could be further boosted by Chimeric Antigen Receptors-engineering, or the combination with cell engagers. For therapeutic approaches, however, it is key to generate large numbers of functional cells.PurposeWe developed a method to efficiently expand adaptive NK cells from NK-enriched cell preparations derived from the peripheral blood of selected CMV-seropositive healthy donors. The method is based on the use of an anti-CD94 monoclonal antibody (mAb) combined with IL-2 or IL-15.ResultsBy setting this method we were able to expand high numbers of NK cells showing the typical adaptive phenotype, CD94/NKG2C+ CD94/NKG2A- CD57+, and expressing a single self-inhibitory KIR. Expanded cells maintained the CMV-induced molecular signature, exhibited high ADCC capabilities and degranulation against a HLA-E+ target. Importantly, mAb-expanded adaptive NK cells did not upregulate PD-1 or other regulatory immune checkpoints that could dampen their function.ConclusionsBy this study we provide hints to improve previous expansion methods, by eliminating the use of genetically modified cells as stimulators, and obtaining effectors not expressing unwanted inhibitory receptors. This new protocol for expanding functional adaptive NK cells is safe, cost-effective and easily implementable in a GMP context, suitable for innovative immunotherapeutic purposes.